The Revision of the IV Phase of EU ETS in the context of the Climate Change Policy Design and Its Implementation - Daniela ZĂNESCU (PANAIT) (Communications of International Proceedings, 2021)
By this paper I scrutinzed whether Romania is on the right path for the fight against climate change and how it stands regarding its target for greenhouse gas emissions reduction as EU Member State. . My contribution to the literature is the brief summary of the Fit 4 55 package and the descriptive analysis of the results of the EU ETS under phase III at EU and national level. Considering the results from phase III in terms of GHG total aggregate emissions, the ETS verified emissions vs. free allocation, EUA price evolution considering quantity based instruments undertaken for the intervention on the volume of EUA in circulation, I  presented the implementation of the current legislative provisions. In this respect I also made a brief evaluation and comments regarding the volatility of the EU allowances prices and the use of the revenues from auctions of EUA. Based on the current research on the functioning of the ETS phase III at national and EU level, this overview may be helpful to guide ETS phase IV efficient implementation, namely in our country. This paper is organized as follows: the abstract gives an overview of the paper and its main conclusions. Section 1 provides the introduction and the background on the European Union Emission Trading Scheme and its main elements as part of the climate change policy design. At the same same time, it presents the latest proposed revision of ETS phase IV. Section 2 summarizes the literature review. Section 3 depict the results of the the current trading phase, at EU and national level. This section also accomodate briefly comments on the EU ETS implemention based on the evaluation of the climate change policy. It also includes a short presentation of the data used for the analysis and my contribution to the literature. Section 4 concludes.
Keywords: Emissions trading; Climate change policy design and evaluation; EU ETS phases